2020
DOI: 10.1093/ej/ueaa024
|View full text |Cite
|
Sign up to set email alerts
|

Health Services as Credence Goods: a Field Experiment

Abstract: Abstract Agency problems are a defining characteristic of healthcare markets. We present the results from a field experiment in the market for dental care: a test patient who does not need treatment is sent to 180 dentists to receive treatment recommendations. In the experiment, we vary the socio-economic status of the patient and whether a second opinion signal is sent. Furthermore, measures of market, practice and dentist characteristics are collected. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 44 publications
3
46
0
Order By: Relevance
“…In real world markets for credence goods, overtreatment is frequently observed (see e.g. Rasch and Waibel, 2017;Baniamin and Jamil, 2018;Gottschalk et al, 2020). Note also that the results from this experimental procedure were successfully replicated by Camerer et al (2016).…”
Section: Energy Efficiency As a Credence Good: A Simple Frameworkmentioning
confidence: 61%
“…In real world markets for credence goods, overtreatment is frequently observed (see e.g. Rasch and Waibel, 2017;Baniamin and Jamil, 2018;Gottschalk et al, 2020). Note also that the results from this experimental procedure were successfully replicated by Camerer et al (2016).…”
Section: Energy Efficiency As a Credence Good: A Simple Frameworkmentioning
confidence: 61%
“…Balafoutas et al (2013Balafoutas et al ( , 2017 show that taxi passengers who reveal that they are unfamiliar with the optimal route to their destination or with the tariff system in the respective city are more likely to be taken on detours and to be overcharged than passengers who simply state the requested destination. Gottschalk et al (2018) report that patients who are perceived as less informed about the proper treatment at a dentist are more likely to be overtreated (with respect to the recommended treatment). All of these papers compare binary information levels and investigate whether changing the information level of consumers has an effect on the behavior of sellers.…”
Section: Formentioning
confidence: 99%
“…The finding that a correct self-diagnosis does not reduce the repair price resembles the result inGottschalk et al (2018) that a second opinion does not reduce overtreatment.23 See, for instance, the New York Times article: https://www.nytimes.com/2011/08/20/technology/finding-fakereviews-online.html?_r=1&ref=todayspaper (accessed on 10 January 2019). 24 See https://www.nytimes.com/2011/05/22/your-money/22haggler.html (accessed on 10 January 2019).…”
mentioning
confidence: 90%
“…The potential impact on credence goods can be seen in the results of a field experiment in the market for dental care of Gottschalk et al [55] where an overtreatment recommendation rate of 28% and a striking heterogeneity in treatment recommendations was observed. It was found that mainly dentists with shorter waiting times are more likely to propose unnecessary treatment than others.…”
Section: Literature Reviewmentioning
confidence: 99%